Qinglong Zhidong Decoction Alleviated Tourette Syndrome in Mice via Modulating the Level of Neurotransmitters and the Composition of Gut Microbiota - Na Wang; Na Wang; Na Wang; Xinchen Wu; Qi Yang; Dingyue Wang; Zhao Wu; Yuanyuan Wei; Jieqiong Cui; Li Hong; Lei Xiong; Dongdong Qin (Frontiers Media S.A., 2022)
Qinglong Zhidong Decoction (QLZDD), a traditional Chinese medicine (TCM) prescription, has been effectively used to alleviate Tourette syndrome (TS) in children. However, the therapeutic mechanism of QLZDD on TS has not been evaluated. The present study aims to elucidate the therapeutic effect and the possible therapeutic mechanism of QLZDD on TS in mouse model. A 3,3-iminodipropionitrile (IDPN, 350 mg/kg)-induced-TS mouse model was established. The mice were randomly divided into the control group, the model group, the haloperidol group (14 mg/kg), the low-, middle-, or high-QLZDD-dose groups (6.83 g/kg, 13.65 g/kg, 27.3 g/kg). QLZDD was administrated orally once a day for 4 weeks. The tic-like behavior was recorded weekly. Then, neurotransmitters and neurotransmitter receptors were analyzed by ELISA, immunohistochemistry (IHC), and quantitative reverse transcription PCR in striatum. Further, the alteration to intestinal flora was monitored by 16s rRNA sequencing, and the role of gut microbiota in the alleviation of TS by QLZDD was investigated. QLZDD ameliorated the tic-like behavior, and decreased the level of excitatory neurotransmitters such as Glu and DA and increased the level of the inhibitory neurotransmitter GABA significantly. Moreover, QLZDD significantly blocked the mRNA expression and the protein expression of D1R and D2R in the striatum, while activated the levels of DAT and GABAR. Interestingly, QLZDD mediated the composition of gut microbiota by increasing the abundance of Lactobacillus and Bacteroides but decreasing the abundance of Alloprevotella and Akkermansia. Taken together, QLZDD ameliorated the tic-like behavior in TS mouse, its mechanism of action may be associated with restoring the balance of gut microbiota and neurotransmitters. The study indicated a promising role of QLZDD in alleviating TS and a therapeutic strategy for fighting TS in clinical settings.